Available nutrient status of a Typic Ustochrept as influenced by two irrigated and rainfed tropical agro-silvicultural plantations - BHADRARAY, SUBHENDU; RAO, Y S; AHMED, N (The Indian Journal of Agricultural Sciences, 2013)
An investigation was done during 1993-94 to study the effect of 10-year old irrigated and rainfed plantations ofEucalyptus tereticornis Smith and Leuceana leucocephala (Lam.) de Wit on available nutrient status of 2 related soil seriesbelonging to Typic Ustochrept with the hypothesis that unless properly managed, those fast growing species maydegrade the soil fertility in a long run, Raising either crops under rainfed condition depleted all the major nutrients and zincover fallow both at the surface and down the profile. Among the plantations Eucalyptus preserved N and K better thanLeuceana while the latter was superior with relation to P and secondary nutrients; micronutrients not showing anydefinite trend. Results could be explained in terms of nutrient demand, nutrient fixation in standing plantations andrenewal through leaf fall and litter formation. Biomass and nutrient harvested/recycled data is expected to provide furtherinsight to the problem. Pot culture experiment with upper 30 cm soil and 'HD 2428' wheat (Triticum aestivum L. emend.Fiori & Paol.) as a test crop corroborated the field study. Soil under irrigated Eucalyptus gave wheat grain yield at par withtreatment having recommended fertilizer dose in fallow while that under Leuceana was significantly lower. Available N,P, K and Zn were found to be important controlling factors towards wheat grain yield.